2017
DOI: 10.3389/fneur.2017.00427
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Composition of Stroke Causing Emboli Correlate with Serum Markers of Atherosclerosis and Inflammation

Abstract: IntroductionThe specific protein composition of stroke-causing emboli is unknown. Because ischemic stroke has a varied etiology, it is possible that the composition of the thrombus from which an embolus originated will have distinctive molecular characteristics reflective of the underlying pathophysiology. We used mass spectrometry to evaluate the protein composition of retrieved emboli from patients with differing stroke etiologies and correlated the protein levels to serum predictors of atherosclerosis.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 8 publications
1
26
0
Order By: Relevance
“…We are aware that an efficient transition from SVM proteome analysis to clinical laboratory tools (e.g., Elisa) could be challenging and time consuming. (12,27). The latter will be possible only when definitive molecular candidate(s) will be confirmed in larger populations with results replicated across stroke centers.…”
Section: Study Limitations and Prospectivesmentioning
confidence: 99%
“…We are aware that an efficient transition from SVM proteome analysis to clinical laboratory tools (e.g., Elisa) could be challenging and time consuming. (12,27). The latter will be possible only when definitive molecular candidate(s) will be confirmed in larger populations with results replicated across stroke centers.…”
Section: Study Limitations and Prospectivesmentioning
confidence: 99%
“…34,38,39,43,45,49 Thrombus composition analysis unveiling pathogenic feature: bacterial signatures, endothelial cells, calcifications, vascular wall components, valve embolisms. 30,45,48,49,50,52,53,56 Correlation studies between thrombus composition analysis, etiology and imaging to predict thrombus stroke etiology even when the thrombus is not extracted. 100 Assessing thrombus age.…”
Section: Thrombus Analysis For Secondary Stroke Preventionmentioning
confidence: 99%
“…Besides histological feature analysis, pilot studies have shown the feasibility of proteomic analysis by mass spectrometry on thrombi, 52,53 as well as studies on RNA sequencing (RNA Sequencing Analysis in Large Vessel Occlusion Stroke DATA Bank, RNASA-LVOSB, NCT03490552) might prospect additional information to differentiate thrombi from patients with varying clinical characteristics. Even bacterial DNA retrieval, as found in coronary thrombi of patients with myocardial infarction undergoing primary percutaneous coronary intervention 41 or peripheral thrombi, 54 might be valuable, although up to now no published study on cerebral thrombi has explored the diagnostic role of bacterial signatures in collected thrombi.…”
mentioning
confidence: 99%
“…and LDL-C may be correlated with in ammation [24]. The high LDL-C/HDL-C ratio may be due to an increase in in ammatory components, a decrease in the anti-in ammatory and antioxidative components re ected in the denominator, or both.…”
Section: Discussionmentioning
confidence: 99%